VOTA OMNIA FINIBVS. La tésera de Herrera de Pisuerga y la ritualización de los pactos en la Hispania indoeuropea (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The tessera from Herrera de Pisuerga (Palencia) records  the  religious sanction of the pacts established at the end of the Augustan Principate between two Indo-european peoples in Hispania. According to the available evidence and parallels, the rituals concerned would be performed in the frontier of the territory  of  the  ciuitas  Maggauiensium  when Amparamus of Cusabura and his family were granted the honorary citizenship of that city.